2018
DOI: 10.3310/phr06010
|View full text |Cite
|
Sign up to set email alerts
|

Cluster randomised controlled trial and economic and process evaluation to determine the effectiveness and cost-effectiveness of a novel intervention [Healthy Lifestyles Programme (HeLP)] to prevent obesity in school children

Abstract: Dean SG, Hillsdon M, et al. Cluster randomised controlled trial and economic and process evaluation to determine the effectiveness and cost-effectiveness of a novel intervention [Healthy Lifestyles Programme (HeLP)] to prevent obesity in school children. Public Health Res 2018;6(1). This journal is a member of and subscribes to the principles of the Committee on Publication Ethics (COPE) (www.publicationethics.org/). Public Health ResearchEditorial contact: journals.library@nihr.ac.ukThe full PHR archive is fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(50 citation statements)
references
References 114 publications
0
50
0
Order By: Relevance
“…Eight economic studies were solely based on diet and nutrition interventions, 31,32,34,38–42 and 15 were nutrition and physical activity based 31,32,35,37,43–53 . The majority of interventions were compared to a usual practice or “do nothing” scenario 31,32,34,36,37,39,42,43,45–47,49–51,53–56 . One intervention was compared to a control condition where the control school was given money to purchase school equipment, 35 and four interventions were compared to usual practice with delayed intervention exposure (e.g., waiting list) 38,44,48,57 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight economic studies were solely based on diet and nutrition interventions, 31,32,34,38–42 and 15 were nutrition and physical activity based 31,32,35,37,43–53 . The majority of interventions were compared to a usual practice or “do nothing” scenario 31,32,34,36,37,39,42,43,45–47,49–51,53–56 . One intervention was compared to a control condition where the control school was given money to purchase school equipment, 35 and four interventions were compared to usual practice with delayed intervention exposure (e.g., waiting list) 38,44,48,57 .…”
Section: Resultsmentioning
confidence: 99%
“…Discussion of non‐intervention costs are discussed further below. Nineteen studies reported an estimate of staff salaries to implement the intervention, training delivery or training receipt 34,37,38,40–42,44–48,50–57 . Nineteen studies included costs of intervention material and material maintenance (where applicable) 31,34,37–43,45,48,50–57 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent studies show no effects on physical activity evaluated with accelerometers in children (Lawlor, El Anderson, Ld Howe, & Moure-Fernandez et al, 2016;Wyatt, Creanor, Green, & Hillsdon et al, 2018), based on the information obtained in this study, which was targeted to six to eight year old children, and included more class activities and intensive family and community interventions, the authors designed and are currently planning a cluster randomized controlled trial. This trial will take into account other variables that may explain the effect on AEE and the time spent in different intensities of physical activity, such as age, sex, nutritional status, school policies, and changes in the physical activity habits of children´s parents and teachers.…”
Section: Gendermentioning
confidence: 99%
“…Furthermore, low levels of PA, high levels of ST, and short sleep durations are all associated with increased food intake and poor diet quality in children (Beaulieu et al, 2016;Chaput and Dutil, 2016;Thivel et al, 2019), with poor diet being a key driver of childhood obesity (Faught et al, 2016). Therefore, future school-based interventions should consider a multidimensional intervention strategy (e.g., PA, sleep, and diet) across settings (e.g., school and home) to achieve sustained effects across the whole day (Love et al, 2018;Wyatt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%